Retromolar canal associated with age, side, sex, bifid mandibular canal, and accessory mental foramen in panoramic radiographs of Brazilians - Capote, Ticiana Sidorenko de O. [UNESP]; Gonçalves, Marcela de Almeida [UNESP]; Campos, Juliana Álvares Duarte Bonini [UNESP] (Hindawi, 2015)
Background. The retromolar canal (RMC) is an anatomical variation that can cause complications in dental procedures. Method. The RMC was evaluated according to age, sex, and presence of accessory mandibular canal and accessory mental foramen, on both sides in 500 panoramic radiographs, belonging to individuals at the age of 7 to 20 years. The associations of interest were studied through Fisher's Exact Test and Pearson's Chi-Square Test, and the correlation was studied through Pearson's Correlation Coefficient (r). The significance level used was 5%. Results. The RMC was observed in 44 radiographs (8.8%), and out of those 24 were females. There was no statistically significant association between the RMC and age (p > 0.05; Fisher's Exact Test), sex (p = 0.787; Pearson's Chi-Square Test), amount of mandibular canals and mental foramina, on both sides (p > 0.05; Pearson's Chi-Square Test). There was a significant association between RMC and side, the higher frequency of the canal being on the right side (p < 0.05; Fisher's Exact Test). Conclusions. Despite the low occurrence of the RMC, its identification and the verification of its dimensions and path are relevant, mainly in cases when anesthetic and surgical procedures can present failures or difficulties.